The Dynamics of Marriage in the Modern Era: Between Tradition and State Law - Irmawaty Nasadi; Suhartin Akadji (Indonesian Civil Law Review, 2025)
The dynamics of marriage in Indonesia reflect the meeting between traditional norms, religious law, and state law regulated in Law Number 1 of 1974 concerning Marriage and its revision through Law Number 16 of 2019. The diversity of this legal system creates its own challenges in realizing legal certainty and justice for all citizens. This study aims to analyze the extent to which national laws on marriage are able to accommodate the social realities and legal pluralism that live in society. The approach used is normative juridical with an analysis of primary legal sources such as laws and regulations, court decisions, as well as academic literature and related legal doctrines. The results of the study show that although national law has provided space for religious and cultural diversity in marriage practices, its implementation in the field is still faced with gaps between legal norms and social practices, especially in marriage registration and the protection of women's and children's rights. For this reason, a more inclusive and responsive legal approach to the socio-cultural context of the community is needed, as well as policy reforms that ensure the protection of basic rights through collaboration between the state, indigenous peoples, and religious institutions. This study recommends a more participatory harmonization mechanism between customary law